Paying more for less: Why don't households in Tanzania take advantage of bulk discounts? - Brian Dillon; Joachim De Weerdt; Ted O'Donoghue (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
Despite average per-capita consumption of roughly 1 per day, many Tanzanian households do not take advantage of bulk discounts for staple goods. Using transaction diaries covering nearly 57,000 purchases by 1,499 households over two weeks, we find that through bulk purchasing the average household could spend 8.9% less on observed quantities (or consume 15.6% more at observed expenditure). We investigate several explanations for the observed purchasing patterns, and find evidence consistent with inattention, worries about over-consumption, avoidance of social taxation, and coordination problems. Contrary to prior work, we find little evidence that liquidity constraints prevent poor households from bulk purchasing.
Keywords: O12; D03; D12; 330; bulk discounts; liquidity constraints; inattention; social taxes; coordination costs; self-control problems; consumer behavior